Validating experiments for the reaction H2 + NH2− by dynamical calculations on an accurate full-dimensional potential energy surface. Issue 17 (14th April 2022) - Song, Kaisheng; Song, Hongwei; Li, Jun
Abstract : Both QCT and QD calculations on a full-dimensional accurate potential energy surface reveal a novel suppression of reactivity by exciting the reactant rotational mode. Abstract : Ion–molecule reactions play key roles in the field of ion related chemistry. As a prototypical multi-channel ion–molecule reaction, the reaction H2 + NH2 − → NH3 + H − has been studied for decades. In this work, we develop a new globally accurate potential energy surface (PES) for the title system based on hundreds of thousands of sampled points over a wide dynamically relevant region that covers long-range interacting configuration space. The permutational invariant polynomial-neural network (PIP-NN) method is used for fitting and the resulting total root mean squared error (RMSE) is extremely small, 0.026 kcal mol −1 . Extensive dynamical and kinetic calculations are carried out on this PIP-NN PES. Impressively, a unique phenomenon of significant reactivity suppression by exciting the rotational mode of H2 is reported, supported by both the quasi-classical trajectory (QCT) and quantum dynamics (QD) calculations. Further analysis uncovers that exciting the H2 rotational mode would prevent the formation of the reactant complex and thus suppress the reactivity. The calculated rate coefficients for H2 /D2 + NH2 − agree well with the experimental results, which show an inverse temperature dependence from 50 to 300 K, consistent with the capture nature of this barrierless reaction. The significant kinetic isotope effect observed by experiments is well reproduced by the QCT computations as well.